Kajian Literatur: Efektivitas Tanaman Kumis Kucing (Orthosiphon Stamineus) sebagai Alternatif Obat Anti-Diabetik - Intan Ardhita; Vriezka Mierza (Jurnal Sehat Mandiri, 2025)
Diabetes mellitus (DM) is one of the degenerative diseases that requires long-term management to maintain stable blood glucose levels. The side effects of conventional antidiabetic drugs have prompted the search for alternative therapies that are safer and more effective. Orthosiphon stamineus (commonly known as Java tea or cat’s whiskers), a herbal plant well-known in Indonesia, contains active compounds such as flavonoids, tannins, and saponins that have potential antidiabetic properties. This article aims to review the potential of Orthosiphon stamineus in lowering blood glucose levels through a literature review of previous research findings. The method used is a literature review by searching databases such as Google Scholar and PubMed using keywords like "Orthosiphon stamineus", "antidiabetic", and "blood glucose." A total of seven relevant scientific journals published between 2015 and 2023 were selected based on topic relevance, full-text accessibility, and the use of both in vitro and in vivo tests. The study results show that Orthosiphon stamineus leaf extract significantly reduces blood glucose levels, inhibits the α-glucosidase enzyme, and enhances GLUT4 translocation and insulin secretion. Conclusion: Cat’s whisker extract (Orthosiphon stamineus) has been proven to significantly reduce blood glucose levels through mechanisms of GLUT4 enhancement, insulin secretion, and α-glucosidase inhibition in diabetic animal models. Further research is recommended to confirm its effectiveness and safety in humans.